Causes of Deforestation of the Brazilian Amazon - Margulis, Sergio (Washington, DC: World Bank, 2013)
The worldwide concern with deforestation of Brazilian Amazonia is motivated not only by the irreversible loss of this natural wealth, but also by the perception that it is a destructive process in which the social and economic gains are smaller than the environmental losses. This perception also underlies the diagnosis, formulation and evaluation of public policies proposed by government and non-governmental organizations working in the region, including the World Bank. The present work suggests that a fuller understanding is necessary with regard to the motivations and identity of the agents responsible for deforestation, the evaluation of the social and economic benefits from the process and the resulting implications of public policies for the region. The objective of the report is to show that, in contrast to the 1970s and 1980s when occupation of Brazilian Amazonia was largely induced by government policies and subsidies, recent deforestation in significant parts of the region is basically caused by medium- and large-scale cattle ranching. Following a private rationale, the dynamics of the occupation process gradually became autonomous, as is suggested by the significant increase in deforestation in the 1990s despite the substantial reduction of subsidies and incentives by government. Among the causes of the transformation are technological and managerial changes and the adaptation of cattle ranching to the geo-ecological conditions of eastern Amazonia which allowed for productivity gains and cost reductions. The fact that cattle ranching is viable from the private perspective does not mean that the activity is socially desirable or environmentally sustainable. Private gain needs to be contrasted with the environmental (social) costs associated with cattle ranching and deforestation. From the social perspective, it is legitimate to argue that the private benefits from large-scale cattle ranching are largely exclusive, having contributed little to alleviate social and economic inequalities. The study notes, however, that decreases in the price of beef in national markets and increases in exports caused by the expansion of cattle ranching in Eastern Amazonia may imply social benefits that go beyond sectoral and regional boundaries.